2011
DOI: 10.1088/0960-1317/21/3/035011
|View full text |Cite
|
Sign up to set email alerts
|

A low-temperature parylene-to-silicon dioxide bonding technique for high-pressure microfluidics

Abstract: We introduce a new low-temperature (280 °C) parylene-to-SiO2 bonding process with high device yield (>90%) for the fabrication and integration of high-pressure-rated microfluidic chips. Pull tests demonstrate a parylene-to-SiO2 bonding strength of 10 ± 3 MPa. We apply this technique for bonding Pyrex and silicon wafers having multiple metal layers to fabricate standard packaged microfluidic devices. By performing electrochemical impedance spectroscopy of electrolyte solutions in such devices, we demonstrate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 43 publications
1
37
0
1
Order By: Relevance
“…patterning by O 2 RIE after photolithography) makes parylene an attractive material for microfluidic channel fabrication and sealing. For example, Ciftlik et al reported bonding strength of 10 and 23 MPa after bonding Pyrex wafers to Parylene C layers deposited on silicon-oxide [108] and silicon-nitride (Fig. 5b) [109], respectively.…”
Section: Sealing Using Adhesive Layersmentioning
confidence: 99%
“…patterning by O 2 RIE after photolithography) makes parylene an attractive material for microfluidic channel fabrication and sealing. For example, Ciftlik et al reported bonding strength of 10 and 23 MPa after bonding Pyrex wafers to Parylene C layers deposited on silicon-oxide [108] and silicon-nitride (Fig. 5b) [109], respectively.…”
Section: Sealing Using Adhesive Layersmentioning
confidence: 99%
“…103 Parylene is a thermoplastic material which has been used in MEMS wafer-bonding processes. 104 The material has been applied to microfluidic device fabrication for bonding glass to glass 105 and glass to silicon 106 at temperatures of 280-350 C. Parylene has seen other microfluidic applications as well. 107,108 The main advantages of Parylene C are its good thermal stability, good chemical resistance, and relatively strong bonding compared with SU-8: pull tests have shown a bonding strength of around 10 MPa and a maximum burst pressure of 7.6 MPa (Ref.…”
Section: Adhesive Bondingmentioning
confidence: 99%
“…107,108 The main advantages of Parylene C are its good thermal stability, good chemical resistance, and relatively strong bonding compared with SU-8: pull tests have shown a bonding strength of around 10 MPa and a maximum burst pressure of 7.6 MPa (Ref. 106). Parylene can be deposited in thin layers by chemical vapour deposition and can be patterned by dry etching through a photoresist mask.…”
Section: Adhesive Bondingmentioning
confidence: 99%
See 1 more Smart Citation
“…São encontradas algumas apresenta baixa constante dielétrica e grande resistência química [64] . As aplicações do Parylene vão de dispositivos da microeletrônica, sensores e dispositivos microfluídicos diversos, com funções de substrato, material de encapsulamento e região ativa para sensores [65,66,67] .…”
Section: O Parylene é O Nome De Um Conjunto De Produtos Derivados Do unclassified